Poemóbiles: leituras em jogo - Gasparetti, Angela Maria (2012)
The main objective of this research is to examine the process of reception of the work Poemóbiles, by Augusto de Campos and Julio Plaza. For that, studies were related to concrete poetry, avant-garde movement of the mid-1950s, and their literary-historical antecedents which greatly contributed to a renewal of poetic language and its legitimacy as original artistic production. We consider the importance of the analysis of poetry and its relation to movement, space and game, elements that expand the possibilities of reading each poem-object. To guide these reflections, we propose as a hypothesis the reading of the work with the abandonment of traditional syntax and the usage of the verse in search of a space syntax, located between the boundaries of literature and the visual arts. Each poem-object considers the word itself, like a living organism, a whole verbivocovisual sensitive, and through the relationship between word and shape of the lightness and displacement of the mobile in space it occupies: this poem-object requires the reader a performative reading. Support for this work was found on studies on: Brazilian Concretism, its origin and theory, by Haroldo and Augusto de Campos and Decio Pignatari, and still on this topic, comprehensive studies by Gonzalo Aguilar; the concept of performance of Paul Zumthor joins the studies on the importance of the conception of movement in the arts of design, crafted by Arlindo Machado; in literary art, the question of space seeks theoretical foundation in Alberto Tassinari; the dialogue between poetry and playfulness is found in the notes of Johan Huizinga and Roger Caillois; the analyzes on the relationship text-reader of Paul Zumthor, of Wolfgang Iser, of Lucia Santaella and others collaborate showing paths, in a way, for the reading of a book-object that dialogs with the visual arts